Anglicans in Rome: Rites of Ecumenical Reconciliation and the Ordination of Women - McLean, Tom (Questions liturgiques, 2024)
This paper considers the state of Anglican-Catholic ecumenical relations as they appear through liturgical celebrations. It considers the celebration of the Eucharist by the Church of England’s Bishop of Fulham at the Lateran Basilica in April 2023 and the celebration of vespers jointly presided over by the Pope and the Archbishop of Canterbury at San Gregorio al Celio in October 2016. Using Mary Douglas’ grid-group cultural theory and the models of ritual reconciliation developed by Victor Turner, Cas Wepener and Kimberly H. Belcher, the paper explores some of the internal tensions within the two churches arising out of ecumenical relations, and the need to re-narrate some of the divisions between them, especially over the ordained ministry of women.